2013
DOI: 10.1093/eurheartj/eht384
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the long-acting nitro vasodilator pentaerithrityl tetranitrate in patients with chronic stable angina pectoris receiving anti-anginal background therapy with beta-blockers: a 12-week, randomized, double-blind, placebo-controlled trial

Abstract: BackgroundThe organic nitrate pentaerithrityl tetranitrate (PETN) has been shown to have ancillary properties that prevent the development of tolerance and endothelial dysfunction. This randomized, double-blind, placebo-controlled, multicentre study (‘CLEOPATRA’ study) was designed to investigate the anti-ischaemic efficacy of PETN 80 mg b.i.d. (morning and mid-day) over placebo in patients with chronic stable angina pectoris.Methods and resultsA total of 655 patients were evaluated in the intention-to-treat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Pre-clinical data suggested that pentaerythrityl tetranitrate may not cause nitrate tolerance (see below) or endothelial dysfunction. However, the drug is not currently commonly used as clinical studies have not shown any clear benefit in patients with chronic, stable angina (60). …”
Section: Preparationsmentioning
confidence: 99%
“…Pre-clinical data suggested that pentaerythrityl tetranitrate may not cause nitrate tolerance (see below) or endothelial dysfunction. However, the drug is not currently commonly used as clinical studies have not shown any clear benefit in patients with chronic, stable angina (60). …”
Section: Preparationsmentioning
confidence: 99%
“…Combination of first line drugs in the treatment of stable angina is more effective than monotherapy in controlling symptoms [26], however depending on baseline systolic blood pressure, and it is important to avoid the combination of beta-blockers with diltiazem or verapamil because of the risk of bradycardia or atrioventicular block [26,27].…”
Section: Beta Blockersmentioning
confidence: 99%
“…For the same reason, PETN was removed in 2012 from the list of reimbursable drugs in Germany, the major market for this drug. The recently concluded Cleopatra study addressed this issue by randomizing 655 patients with coronary artery disease to receive placebo or two daily doses of 80 mg of PETN, demonstrating a benefit of PETN on exercise tolerance during a 12-weeks treatment [ 76 ]. These data will hopefully lead to reconsider the use of (and further research on) this drug in clinical practice worldwide.…”
Section: Pentaerythrityl Tetranitrate (Petn)mentioning
confidence: 99%